Animal Farm Revisited: An Environment Allegory - Pardy, Bruce (Victoria University of Wellington Law Review, 1999)
In 1945, George Orwell wrote Animal Farm, a story about barnyard animals who overthrow their tyrannical human master but end up creating an equally oppressive hierarchy. "All animals are equal", reads the seminal line in the book, "but some animals are more equal than others". Animal Farm was an allegory about the Soviet Union under Stalin, although Orwell intended it to have wider application also. "It is" wrote Orwell in the blurb for the first edition, "the history of a revolution that went wrong – and of the excellent excuses that were forthcoming at every step for the perversion of the original doctrine". In "Animal Farm Revisited" Orwell's template has been applied to the environmental question. In a multitude of countries, including New Zealand, and in the international sphere, environmental law suffers from a plethora of good intentions and a paucity of concrete principles. Indeed, the history of environmental protection could be described as the story of an intention gone astray – and of the excellent explanations that have been forthcoming for the qualification of its purpose. "Animal Farm Revisited" is a kind of environmental Rorschach test: at what moment do actions become environmentally inappropriate? Many answers are possible. The story is not specifically about the Resource Management Act 1991, but its themes are relevant to the Act and its interpretation.